STRATEGI MANAJEMEN PERUBAHAN MELEK TEKNOLOGI DALAM MEMBANGUN UMKM TECHNOPRENEUR (Jurnal Manajemen dan Ekonomi (JME), 2023)
The synergy of MSME actors with academics, in this case, universities and local governments is a new thing in facing the challenges of digitalization to grow technopreneur-based entrepreneurs. The presence of Hipmi which was formed as a representative of the Indonesian Young Entrepreneurs Association in each region can be a forum for business people to realize the management of changes that were originally conventional business activities to technology-based. The purpose of the study was to determine the change management strategy in building Technopreneur MSMEs. Based on data from the Ministry of Communication and Information in 2020, it was recorded that the existence of MSMEs increased but was not accompanied by businesses that utilize digital roles. This is certainly very influential on the sustainability of MSMEs themselves. The continuity of MSMEs in the context of entrepreneurship requires transformative acceleration towards technopreneurship and is supported by resource competencies in fostering innovation and creativity. This can be overcome by creating collaboration between universities and the government with existing Hipmi which is a pillar of academic communication, MSMEs and across parties and institutions that want to play a more active role in change management.
Keywords: Change management; MSME; Technopreneur